Analisis Quality Of Service (QOS) Jaringan Outdoor 4G di Perumahan Royal Madinah Kabupaten Lombok Barat dengan Metode Drive Test - Muhammad Fajri; Suthami Ariessaputra; Abdullah Zainuddin; Sudi Mariyanto Al Sasongko; Cahyo Mustiko Okta Muvianto (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2023)
Humans need access to information through cellular technology to support their activities, and will continue to increase with the times. This condition forces cellular service providers to continue to innovate to maintain quality to meet the various needs of their users, including in residential areas. Cellular service quality in housing can be determined using Quality of service (QoS) measurements, one of which is the Royal Medina housing complex in West Lombok Regency. The measurements of Quality of service values and signal level values are using the Wireshark and G-Nettrack Pro applications. In addition, measurements use the drive-test method. Based on the THIPON standard, the outdoor measurement results show that the throughput value is in a bad category, while the delay value is in the medium and bad category.